The Lover and its Own. A Political Reading of Max Stirner - Yague, Pedro Guillermo (Las Torres de Lucca. International Journal of Political Philosophy, 2020)
Reading the work of Max Stirner usually it is found conditioned by the critique of Marx and Engels. His texts are however rich in theoretical subtleties and nuances. One of the guidelines developed by Stirner and not sufficiently discussed by the authors of La ideología alemana is its conceptualization around love as a key to understand the political association of Men. As part of a conceptual constellation in which notions such as interest or property play a fundamental role, love appears in El Único y su propiedad as a key passion from which different types of relationships between them are explained. Stirner attempts to answer why men alienate their individuality in their own creations from an approach to the sensitive materiality of the desire of men distancing from each other. In this paper I propose to take up this dimension of analysis of Max Stirner in order to highlight the importance of a political reading of his work beyond Marx’s and Engel’s critique.